THE IMAGE OF A WOMAN IN THE LITERATURE OF DIFFERENT ERAS (Web of Teachers: Inderscience Research, 2024)
The article examines the types of female images and stereotypes of their behavior, as well as the peculiarity of the nature of women in Russian literature. The article is devoted to the study of the specifics of the types of female images and their social role in world literature and to trace how the image of a woman in Russian literature has changed over the centuries.